Evaluasi Program Pendidikan di SMK PGRI 7 Surabaya - Hadrianingtyas, Balqis; Aisyah, Nesha; Zhulhijjah, Sheila; Amalia, Kaniati (Lembaga Yasin AlSys, 2024)
Minister of National Education Regulation of the Republic of Indonesia Number 20 Year 2007 regarding education assessment standards describes that educational assessment is a process of collecting and processing information to assess students' learning achievements. At SMK PGRI 7 Surabaya, a teacher conducts evaluation to assess students' performance in carrying out their tasks. This research uses a qualitative approach, conducting interviews and participatory observation, as well as recording data in the form of audio recordings, images, and field notes. The research results indicate that SMK PGRI 7 Surabaya implements the Final Summative Assessment Program (PSAJ) only in grade 12. The purpose of this program is to evaluate all aspects of assessment at the end of the educational level. PSAJ evaluation is conducted by the school, and the results are determined by the school itself. However, there are several issues related to the implementation of PSAJ, such as the lack of standard values, difficulties in motivating learning, and recruiting special guidance teachers (GPK).